Vocal behaviour of the Great Cormorant Phalacrocorax carbo sinensis during the breeding season. Issue 2 (3rd April 2021) - Mäkelin, Saara; Wahlberg, Magnus; Osiecka, Anna N.; Hermans, Claire; Balsby, Thorsten J.S.
ABSTRACT: Capsule: Great Cormorants Phalacrocorax carbo sinensis use vocal communication during the breeding season, with males being particularly vocal earlier in the breeding cycle and showing individual variation in some calls, which could be used for individual recognition. Aims: To identify and describe vocal behaviour of Great Cormorants, to link calls with observed behaviours and to explore if the calls had potential for individual recognition. Methods: We followed 21 nesting pairs of Great Cormorants by videoing and recording their vocal behaviour throughout the breeding season. We linked calls with observed behaviours, and measured the acoustic characteristics of the calls using signal analysis tools in Matlab. Results: We identified and measured acoustic characteristics of six different call types: courtship, landing, nest building, nest relief, jumping, and chick begging calls. Five of these call types were linked to distinctive breeding behaviours. Vocal signalling occurred between the male and female, and between parents and offspring. Males showed higher vocal activity than females and used a larger repertoire of calls. The courtship call was the most common call type in both sexes. These calls also differed acoustically between the sexes; male calls were longer in duration than female calls (617 ms versus 323 ms) and had wider bandwidth (763 Hz versus 473 Hz). Conclusion: Great Cormorants use vocal communication for social interactions. Males were vocally more active and had a larger repertoire of calls than females, and calls differed between the sexes. Calls of males also differed individually and could, therefore, function for individual recognition in this species.